Ethanol sclerotherapy for venous malformation. Issue 10 (2nd September 2014) - Steiner, Frederica; FitzJohn, Trevor; Tan, Swee T.
Abstract: Background: Ethanol sclerotherapy (ES) is the preferred treatment for venous malformation (VM) with surgery playing an adjunctive role. Results of ES, however, are not well documented in the literature. Methods: VM patients were identified from our vascular anomalies database from 1996 to 2011. After treatment completion, patients completed questionnaires evaluating symptoms and their severity and effect on appearance, function and overall quality of life (QoL), before and >6 months after treatment, using visual analogue scales of 0–10. Patients rated their overall satisfaction with ES using a scale of 0–10. Results: Fifty‐four (23.9%) of the 226 VM patients underwent a total of 90 ES sessions (average 1.7 sessions per patient). Complications occurred in 12 (22.2%) patients in 12 (13.3%) ES sessions. Minor complications occurred in nine (16.7%) patients including transient paraesthesia ( n = 3), transient weakness of facial nerve branch(es) ( n = 3), skin blistering ( n = 2) and spontaneously healing ulceration ( n = 1). Major complications occurred in three (5.6%) patients in three (3.3%) ES sessions including skin necrosis ( n = 1), Horner's syndrome ( n = 1) and finger paraesthesia with joint stiffness ( n = 1). ES improved the severity of background pain, episodic pain, contour deformity and skin discoloration in 86.0%, 72.4%, 83.0% and 72.2% of patients respectively. It reduced the effect of VM on appearance, function and overall QoL in 69.8%, 73.0% and 64.3% of patients. Mean treatment satisfaction was 7.9 (range, 0–10). Conclusion: ES reduces pain, contour deformity and skin discoloration, and improves appearance, function and QoL. Our complication rates are consistent with the literature.